Hubungan Tingkat Pengetahuan Bahaya Merokok dengan Perilaku Merokok di Pondok Pesantren Mahasiswa UNSIQ - Rohman, Aly; Azam Mustajab, Abdullah; Mulyani, Sri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Smoking habits have become a lifestyle for all groups from old to young, even among children. The prevalence of smokers in Indonesia is quite high with 69.1 million adult smokers. The environment of cigarette smoke causes several diseases such as heart disease, lung cancer, and the risk of laryngeal neoplasm. Supporting factors for someone to choose which actions are good and bad, especially smoking behavior is influenced by knowledge. The aim is to determine the relationship between the level of knowledge of the dangers of smoking and smoking behavior at the UNSIQ Male Student Islamic Boarding School. The research method uses an observational correlation design with a Cross Sectional approach. The study population was 40 students, the research sample with total sampling. Data analysis using the Spearman-Rank test to determine the relationship between the level of knowledge of the dangers of smoking and smoking behavior. The results of this study obtained 13 respondents with good knowledge, 15 moderate, and 12 low, while the behavior of respondents as many as 20 respondents had high smoking behavior and 20 had moderate smoking behavior, and the p-value results were 0.100> 0.05. The conclusion is that there is no relationship between the level of knowledge and smoking behavior at UNSIQ Male Student Islamic Boarding School.